Measures Matter: A Meta-Analysis of the Effects of Educational Apps on Preschool to Grade 3 Children's Literacy and Math Skills. (April 2021) - Kim, James; Gilbert, Joshua; Yu, Qun; Gale, Charles
Thousands of educational apps are available to students, teachers, and parents, yet research on their effectiveness is limited. This meta-analysis synthesized findings from 36 intervention studies and 285 effect sizes evaluating the effectiveness of educational apps for preschool to Grade 3 children and the moderating role of methodological, participant, and intervention characteristics. Using random effects meta-regression with robust variance estimation, we summarized the overall impact of educational apps and examined potential moderator effects. First, results from rigorous experimental and quasi-experimental studies yielded a mean weighted effect size of +0.31 standard deviations on overall achievement and comparable effects in both math and literacy. Second, the positive overall effect masks substantial variability in app effectiveness, as meta-regression analyses revealed three significant moderators of treatment effects. Treatment effects were larger for studies involving preschool rather than K–3 students, for studies using researcher-developed rather than standardized outcomes, and for studies measuring constrained rather than unconstrained skills.